2023
DOI: 10.3390/vaccines11020385
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Healthcare Workers in Israel towards the Fourth Dose of COVID-19 Vaccine

Abstract: Attitudes of healthcare workers (HCWs) toward vaccines are extremely important for increasing vaccination coverage. We conducted a cross-sectional study at the beginning of the fourth COVID-19 vaccination dose campaign among 124 HCWs to evaluate attitudes towards the fourth dose and willingness to get vaccinated. At that time, Israel was the first country to approve the fourth vaccine dose. Most women were unwilling to get the fourth vaccine dose compared to men; 53.9% of physicians were unwilling to get vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Data from Singapore showed that hesitancy in nurses (15 [7.4%]) was higher than for staff in medical (0%) and applied health (5 [3.5%]) [ 45 ] professions. A cross-sectional study among Israel healthcare workers showed that 83.3% of nurses were against the fourth dose [ 19 ]. Possible explanations might include more concerns about vaccine effectiveness and safety, and less knowledge about the vaccine among nurses [ 48 ], since nurses were less likely to have a higher education background among the different professions of our participants ( Table S6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from Singapore showed that hesitancy in nurses (15 [7.4%]) was higher than for staff in medical (0%) and applied health (5 [3.5%]) [ 45 ] professions. A cross-sectional study among Israel healthcare workers showed that 83.3% of nurses were against the fourth dose [ 19 ]. Possible explanations might include more concerns about vaccine effectiveness and safety, and less knowledge about the vaccine among nurses [ 48 ], since nurses were less likely to have a higher education background among the different professions of our participants ( Table S6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data from Singaporean public primary care clinics showed that vaccine hesitancy among healthcare workers had improved from the first dose to CBV [ 18 ]. A cross-sectional study at the beginning of the fourth COVID-19 vaccination dose campaign in Israel showed that 53.9% of physicians were unwilling to be vaccinated compared to 83.3% of nurses and 69% of other healthcare professions, with the most frequent concerns regarding the vaccine being its efficacy, benefit, and necessity [ 19 ]. In the present study, we aimed to explore the prevalence and determinants of future CBV refusal at this particular time point.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted during lockdown in Israel before the COVID-19 vaccine was distributed had reported that the level of willingness to be vaccinated was higher among physicians than nurses [ 47 ]. Another study conducted in Israel has reported that 53.9% of physicians were unwilling to get vaccinated with the fourth COVID-19 booster dose, compared to 83.3% of nurses [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“… 7 A dose-response relationship has been observed where increasing proportions of vaccine-hesitant individuals within one’s social network corresponded to lower likelihoods of personal vaccine acceptance. 8 …”
Section: Introductionmentioning
confidence: 99%
“… 17 A fourth dose of COVID-19 vaccination has been approved in Israel and Japan in May 2022, mainly for healthy adults who received the third vaccination more than five months ago. 8 , 18 China is also considering initiating a fourth vaccination at an appropriate time in response to a COVID-19 pandemic. 19 The aim of this study was to assess the relationship between hesitancy and friends of Chinese healthcare workers regarding the fourth booster vaccination in the context of social reopening.…”
Section: Introductionmentioning
confidence: 99%